2009
DOI: 10.1111/j.1365-313x.2008.03697.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of salicylic acid glucosyltransferase, OsSGT1, to chemically induced disease resistance in rice plants

Abstract: Summary Systemic acquired resistance (SAR), a natural disease response in plants, can be induced chemically. Salicylic acid (SA) acts as a key endogenous signaling molecule that mediates SAR in dicotyledonous plants. However, the role of SA in monocotyledonous plants has yet to be elucidated. In this study, the mode of action of the agrochemical protectant chemical probenazole was assessed by microarray‐based determination of gene expression. Cloning and characterization of the most highly activated probenazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 45 publications
0
54
1
Order By: Relevance
“…In Arabidopsis, overexpression of SAGT led to increased susceptibility to Pseudomonas syringae (Song et al 2008). Umemura et al proposed that SAG possibly contributes to SAR by serving as a natural regulator in rice plant (Umemura et al 2009). We found that the signal intensity of SAG decreased proportionally along with the ABA treatment period and the ABA concentration regardless of the SA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, overexpression of SAGT led to increased susceptibility to Pseudomonas syringae (Song et al 2008). Umemura et al proposed that SAG possibly contributes to SAR by serving as a natural regulator in rice plant (Umemura et al 2009). We found that the signal intensity of SAG decreased proportionally along with the ABA treatment period and the ABA concentration regardless of the SA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, involvement of SA glucosyltransferase which converts SA to its glucoside in chemical induction of defense mechanism has been demonstrated in rice plants. 14 At gene expression level (examining the SA-responsive gene expression with micro-array) 15 and molecular genetic level (using SA-related mutant cell lines), 7 involvement of SA signal transduction pathway in O 3 response in Arabidopsis thaliana have been proven.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the production of rOsTAGG2P The culture medium of the transformant of P. pastoris carrying the expression cassette for OsTAGG2 showed 0.5 U/mL after induction at 30 C for 96 h, but the enzyme produced barely adsorbed onto a Ni-chelating Sepharose column (data not shown). His 6 -tag antibodies detected no band in the non-adsorbed fraction, suggesting that the His 6 -tag has been removed or destroyed during culture.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were collected by centrifugation and suspended in 10 mL of BMMY medium (10 mg/mL of glycerol in BMGY was changed to 0.5% v/v methanol). The cell suspension was further incubated at 30 C for 96 h. Protein production was maintained by the addition of methanol at a final concentration of 0.5% v/v every 24 h. The enzyme activity of the culture supernatant of each transformant was measured as described below. The transformant with the highest productivity of recombinant OsTAGG2 was selected for further analysis.…”
Section: Methodsmentioning
confidence: 99%